توظيف التناص في رواية قد شغبها حبا لنردين أبو نبعة - غرغوط, بن الشهبة, مروة سارة (University of El-oued, 2021)
في ظل تبلور مفهوم التناص في الدراسات الغربية الحديثة ثم في الدراسات العربية الحديثة عرف الخطاب الشعري العربي المعاصر جملة من التفاعلات النصية على المستويين التشكيلي والدّلالي فكان انفتاحهما على أكثر من صعيد, انفتاح على النص الأسطوري والتّاريخي وانفتاح على ذاكرة شعريّة ممتدة في الزمان لتشمل متن الخطاب الشعري القديم والحديث وأنواع الخطاب اللاشعري والحكم ونصوص النشر والكلام اليومي بالإضافة إلى القرآن الكريم والحديث النبوي الشريف اللذين يشكلان المرجعية البكر للشاعر العربي القديم والمعاصر على حد سواء. من هنا كان ولوجنا نحو ظاهرة التّناص بإعتباره ذات أصول عريقة في تراثنا النقدي, بادرت العديد من الإتجاهات الأدبية والمدارس النقدية المعاصرة إلى بلورتها, وهذا ما دفعنا إلى البحث عن مفهومه ومدى توظيفه في الرواية العربية ووقع إختيارنا على رواية "قد شغفها حبا" لنزدين أبو نبعة, فقد عنونا مذكرتنا بتوظيف التّناص في رواية قد شغفها حبا لنردين أبو نبعة. In light of the crystallization of the concept of intertextuality in modern Western studies and then in modern Arab studies, the contemporary Arab poetic discourse knew a number of textual interactions on the plastic and semantic levels. Their openness was on more than one level, an openness to the legendary and historical text and an openness to a poetic memory extended in time to include the body of poetic discourse. The ancient, the hadith, types of non-poetic discourse, judgment, publication texts, daily speech, in addition to the Noble Qur’an and the Noble Prophetic hadith, which constitute the pristine reference for the ancient and contemporary Arab poet alike. Hence, our access to the phenomenon of intertextuality as it has deep roots in our critical heritage, many literary trends and contemporary critical schools took the initiative to crystallize it, and this is what prompted us to search for its concept and the extent of its use in the Arabic novel. , they titled our memoir by employing intertextuality in a novel that he loved for the love of Nardin Abu Nabaa.
Keywords: intertextuality - narration - Nardin Abu Baya. Poetry - prose; التناص – الرواية – نردين ابو بيعة. الشعر- النثر